The effect of the addition of silanated poly propylene fiber to polymethylmethacrylate denture base material on some of its mechanical properties - Ismaeel, Intisar J; Alalwan, Hasanain KA; J, Mustafa M (Journal of Baghdad College of Dentistry, 2015)
Background: Poly propylene fibers with and without silane treatment have been used to reinforce heat cure denture base acrylic but, some mechanical properties like transverse strength, impact strength, tensile strength, hardness, wear resistance and wettability. Which are related to the clinical use of the prosthesis are not evaluated yet. The aim of the study is to identify the influence of incorporation of treated and untreated fibers on these properties Materials and methods: Eighty four heat cure acrylic specimens were constructed by conventional flasking technique. They were divided into six groups according to the tests and each group was subdivided into two subgroups control and experimental groups (seven samples for each subgroup).Transversestrength and Tensile strength test were performed using Instron universal testing machine. The impact strength test was evaluated by the use of Impact testing device. Wear resistance was evaluated by pin on disk wear measurement method while, a digital microscope supplied with high resolution camera was utilized to measure the contact angle reflecting wettability grade. Descriptive statistics and independent t test were used for statistical significance. Results:The results revealed that the addition of Silanated polypropylene fibers produced significant difference in transverse strength and highly significant difference in tensile strength, the impact strength,Wettability value compared with the control group also the results showed that the hardness test was not significant and different control group . Wear resistance was highly significant decreased in experimental groups Conclusion: Incorporation of silanated treated Poly propylene fibers to heat cure Poly methyl methacrylate resin was beneficial regarding the tested properties to improve the mechanical properties of the resin. Key words: Poly propylene fibers, transverse strength, impact strength, tensile strength, hardness, wear resistance, wettability.